Fiscal Policy segregation in the inflation targeting scheme - León León, Josefina (2019)
Fiscal policy enjoyed great popularity during the post-war period as the main tool of macroeconomic stability. With the passage of time it began to lose relevance, being relegated only to stabilize the cycles. The objective of this paper is to review why fiscal policy has been relegated to a second place within theoretical analyses and to analyze its “implicit” role in the New Macroeconomic Consensus. While it is true that monetary policy has been responsible for creating the necessary conditions to generate stability, fiscal policy is crucial to reach the objective on the inflation rate.